2022
DOI: 10.1021/acs.jpcb.2c02476
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Dipole Potential: An Emerging Approach to Explore Membrane Organization and Function

Abstract: Biological membranes are complex organized molecular assemblies of lipids and proteins that provide cells and membrane-bound intracellular organelles their individual identities by morphological compartmentalization. Membrane dipole potential originates from the electrostatic potential difference within the membrane due to the nonrandom arrangement (orientation) of amphiphile and solvent (water) dipoles at the membrane interface. In this Feature Article, we will focus on the measurement of dipole potential usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 183 publications
0
9
0
Order By: Relevance
“…Membrane dipole potential, originating from the preferential alignment of interfacial water molecules and the anisotropic orientation of lipid dipolar moieties, can reach high values of up to several hundred millivolts, leading to the formation of a strong, local electric field. It is thus of no surprise that such a dipole potential is very effective in modulating the conformation and function of membrane proteins as well as their distribution and binding affinity. , It has been shown that the membrane dipole potential is not homogeneouson the contrary, it is significantly larger in lipid domains enriched in cholesterol, correlating well with the localization of lipid raft markers within the membrane . Crucially, the spatial heterogeneity of the membrane dipole potential is interweaved with its temporal variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane dipole potential, originating from the preferential alignment of interfacial water molecules and the anisotropic orientation of lipid dipolar moieties, can reach high values of up to several hundred millivolts, leading to the formation of a strong, local electric field. It is thus of no surprise that such a dipole potential is very effective in modulating the conformation and function of membrane proteins as well as their distribution and binding affinity. , It has been shown that the membrane dipole potential is not homogeneouson the contrary, it is significantly larger in lipid domains enriched in cholesterol, correlating well with the localization of lipid raft markers within the membrane . Crucially, the spatial heterogeneity of the membrane dipole potential is interweaved with its temporal variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus of no surprise that such a dipole potential is very effective in modulating the conformation and function of membrane proteins as well as their distribution and binding affinity. 25,26 It has been shown that the membrane dipole potential is not homogeneous�on the contrary, it is significantly larger in lipid domains enriched in cholesterol, correlating well with the localization of lipid raft markers within the membrane. 79 Crucially, the spatial heterogeneity of the membrane dipole potential is interweaved with its temporal variation.…”
Section: ■ Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on these findings, it is reasonable to assume that Dabcyl might be able to reduce the membrane dipole potential and thereby enhance the cellular uptake of peptides. However, in the case of the shorter Dabcyl-conjugated oligoarginines, which enter cells mainly via lipid raft-mediated endocytosis, there is an apparent contradiction: treating cells with mBCD lowers the membrane dipole potential [43], yet the uptake of peptides is reduced. Therefore, it is an interesting question as to what is the mechanism by which Dabcyl exerts its special effect.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the fluorescence intensity decreases at low wavenumber and increases at high wavenumber, and the ratio of the two intensities represents a measure of the probe's response to the electric field. 95,99 For example, Haldar et al designed a voltage-sensitive probe molecule of 4-(2-(6-(dioctylamino)-2-naphthalenyl)ethenyl)-1-(3-sulfopropyl)-pyridinium inner salt (di-8-ANEPPS), which is mainly characterized by the hydrophilic receptors and two hydrocarbon chains, making the fluorescent groups parallel to the lipid molecules (Fig. 5c).…”
Section: Monitoring and Investigation Of Self-assemblymentioning
confidence: 99%